Manajemen Tahfidzul Quran pada Santri Lansia - Musafak, Musafak (Jurnal Studi Islam dan Kemuhammadiyahan (JASIKA), 2022)
Pondok Pesantren is an Al Munawwar Islamic Boarding School which has a concept by focusing on Tahfidzul Qur'an, the problem in the Tahfidz Al-Qur'an program is in the elderly learning process, it can be seen from the inappropriateness of the methods used in Tahfidz Al-Qur'an learning management. Qur'an. The purpose of this study was to determine the natural setting of the Al Munawwar Islamic Boarding School, planning, organizing, implementing, monitoring, supporting and inhibiting factors, as well as the results achieved in Tahfidz Al-Qur'an learning management. This research method uses a descriptive-qualitative approach which is used through interviews, observation and documentation studies or copying. The results of this study concluded that the Islamic boarding school Al-Islamic boarding school Al Munawwar is an Islamic foundation based on tahfidzul Qur'an. Planning is carried out with four stages of selection, organizing by determining tasks and mechanisms in the learning process, implementation is marked by the existence of a teaching and learning process, supervision by monitoring the student deposit book and attending students, the supporting factor is from the boarding school environment, which hinders the lack of istiqomah santri elderly in memorizing tahfidz al-Qur'an. And the success achieved by the Al Munawwar Islamic Boarding School can be seen from the results of achievements by participating in the Tahfidz Al-Qur'an competition at various levels and championships. Keyword : Al Munawwar ; Management;